2015
DOI: 10.1186/s13071-015-0811-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses and intestinal injury development during acute Trypanosoma cruzi infection are associated with the parasite load

Abstract: BackgroundChagas disease is caused by the protozoan Trypanosoma cruzi and is characterized by cardiac, gastrointestinal, and nervous system disorders. Although much about the pathophysiological process of Chagas disease is already known, the influence of the parasite burden on the inflammatory process and disease progression remains uncertain.MethodsWe used an acute experimental disease model to evaluate the effect of T. cruzi on intestinal lesions and assessed correlations between parasite load and inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 45 publications
4
36
0
4
Order By: Relevance
“…This inflammatory process was demonstrated in this study by the presence of inflammatory foci in the colonic wall. Trypanosoma cruzi infected mice usually have intense inflammatory foci in the colonic wall even during the chronic phase of the infection, as we also found in the infected mice treated with PBS. However, we found reduction of the number of inflammatory foci in T. cruzi infected mice treated with ASA during acute or chronic phases.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This inflammatory process was demonstrated in this study by the presence of inflammatory foci in the colonic wall. Trypanosoma cruzi infected mice usually have intense inflammatory foci in the colonic wall even during the chronic phase of the infection, as we also found in the infected mice treated with PBS. However, we found reduction of the number of inflammatory foci in T. cruzi infected mice treated with ASA during acute or chronic phases.…”
Section: Discussionsupporting
confidence: 82%
“…We evaluated the level of NO in the colonic tissue since T. cruzi induces upregulation of NO production in several tissues . We observed that the level of NO was reduced in infected mice treated with PBS, possibly due to the intense loss of nitrergic myenteric neurons and also because the inflammatory foci in the colonic wall did not stimulate release of interferon gamma (IFN‐γ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Lenzi [10] demonstrated the relationship between the disseminated form of infection, tissue damage in the acute phase and the presence of the parasite in the tissue. Other authors have also described the relationship between T. cruzi parasitism and acute infection in other organs, such as the kidney and intestines [11][12][13].…”
Section: Introductionmentioning
confidence: 99%